2021
DOI: 10.1080/14397595.2021.1918864
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of therapeutic effects of combination therapy with prednisolone and tacrolimus or azathioprine on progressive interstitial pneumonia with systemic sclerosis

Abstract: Objectives We retrospectively compared the therapeutic effects of combination therapy with prednisolone (PSL) and oral tacrolimus (TAC) or azathioprine (AZA) on progressive interstitial pneumonia with systemic sclerosis (SSc-PIP). Methods The effects of PSL (0.2–0.5 mg/kg/day) and TAC (3 mg/day) or AZA (1–2 mg/kg/day) therapies (n = 18) were evaluated for short (12 months) and long (36 months or more) periods. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 27 publications
0
5
0
Order By: Relevance
“…2 A better understanding of the underlying mechanism of childhood pneumonia could contribute to the development of an effective and novel treatment to overcome this burden. 3,4 Fighting infection is the primary need toward treating pneumonia. Since pneumonia is a disease caused by a variety of pathogenic microorganisms infecting the lung parenchyma, anti-infective drugs are the first choice for its treatment.…”
Section: Introductionmentioning
confidence: 99%
“…2 A better understanding of the underlying mechanism of childhood pneumonia could contribute to the development of an effective and novel treatment to overcome this burden. 3,4 Fighting infection is the primary need toward treating pneumonia. Since pneumonia is a disease caused by a variety of pathogenic microorganisms infecting the lung parenchyma, anti-infective drugs are the first choice for its treatment.…”
Section: Introductionmentioning
confidence: 99%
“…SSc-associated ILD and PAH are severe complications with poor prognoses. A clinical study indicated that TAC effectively reduces ILD progression and improves lung function in patients with SSc ( 6 ). This study presents innovative therapeutic strategies for patients with SSc complicated by ILD and PAH, highlighting the potential benefits of TAC not only in inhibiting fibrosis but also in potentially ameliorating PAH through the upregulation of BMPR2.…”
mentioning
confidence: 99%
“…As highlighted by Huang and colleagues, the downregulation of the BMPR2 signaling pathway is pivotal in the development of pulmonary arterial hypertension (PAH) in systemic sclerosis (SSc) ( 2 ). The evidence suggesting that tacrolimus can improve fibrosis progression and lung function in patients with SSc further underscores its therapeutic potential ( 3 ). Notably, tacrolimus can restore BMPR2 signaling across a spectrum, from lower concentrations (0.2–2 ng/ml) to elevated levels (>5 ng/ml, within the immunosuppressive range) ( 4 ).…”
mentioning
confidence: 99%